Microglia target synaptic sites early during excitatory circuit disassembly in neurodegeneration - Alfred Yu; Camille Fang; Li Xuan Tan; Aparna Lakkaraju; Luca Della Santina; Yvonne Ou (iScience)
Summary: During development, microglia prune excess synapses to refine neuronal circuits. In neurodegeneration, understanding the role of microglia-mediated synaptic pruning in circuit remodeling and dysfunction is important for developing therapies aimed at modulating microglial function. Here, we analyzed microglia-mediated synapse disassembly of degenerating postsynaptic neurons in the inner retina. After inducing transient intraocular pressure elevation to injure retinal ganglion cells, microglia increase in number, shift to hyper-ramified morphology, and exhibit greater process movement. Furthermore, due to the greater number of microglia, there is increased colocalization of microglia with synaptic components throughout the inner plexiform layer and with excitatory synaptic sites along individual ganglion cell dendrites. Microglia depletion partially protects ganglion cell function, suggesting that microglia activation may be neurotoxic in early neurodegeneration. Our results demonstrate the important role of microglia in synapse disassembly in degenerating circuits, highlighting that microgliosis is the primary mechanism for increased synapse colocalization early after neuronal injury.